2021
DOI: 10.1007/s00726-021-03048-x
|View full text |Cite
|
Sign up to set email alerts
|

Isozymes of P5C reductase (PYCR) in human diseases: focus on cancer

Abstract: Δ 1 -Pyrroline-5-carboxylate (P5C) reductase (PYCR or P5CR) catalyzes the conversion of P5C to L-proline (Pro) with concomitant oxidation of a cofactor, NADPH or NADH. Mammalian PYCR have been studied since 1950' and currently three isozymes of human PYCR, 1, 2, and L, have been identified and characterized and their roles in genetic diseases and cancer biology have been keenly investigated. These three isozymes are encoded by three different genes localized at three different chromosomes, and catalyze NAD(P)H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Furthermore, PYCR3 is cytosolic and prefers NADPH whereas PYCR1/2 prefer NADH and are located in mitochondria matrix. The central role of the PYCRs is emphasized by recent reviews (Li et al 2021 ; Hu 2021 ; Bogner et al 2021 ).…”
Section: Proline Metabolism and Cancermentioning
confidence: 99%
“…Furthermore, PYCR3 is cytosolic and prefers NADPH whereas PYCR1/2 prefer NADH and are located in mitochondria matrix. The central role of the PYCRs is emphasized by recent reviews (Li et al 2021 ; Hu 2021 ; Bogner et al 2021 ).…”
Section: Proline Metabolism and Cancermentioning
confidence: 99%
“…Three PYCR isoforms have been identified in the human body, which are products of three homologous genes: PYCR1 (17q25.3), PYCR2 (1q42.13), and PYCRL (8q24.3.7) [ 30 ]. PYCR1 and PYCR2 show 84% structural homology and are located in the mitochondrial intermembrane space and mitochondrial matrix, respectively [ 57 ]. They are mainly involved in the conversion of P5C to proline, in the glutamine-P5C-proline pathway.…”
Section: Enzymes Of the P5c Metabolismmentioning
confidence: 99%
“…Evidence for the involvement of PYCR1 in cancer mechanisms is growing rapidly. Several studies have implicated PYCR1 in cancer across various cancer types, including colorectal cancer, multiple myeloma, kidney cancer, , liver cancer, prostate cancer, lung cancer, breast cancer, and others. , Many studies have shown that high PYCR1 expression is associated with tumor aggressiveness and poor patient outcomes. , ,,, Furthermore, the knockdown of the PYCR1 gene or the inhibition of PYCR1 enzyme has been shown to inhibit tumorigenesis in multiple cancer cell lines and in vivo animal models. ,,, ,,,,,, Mechanistically, PYCR1 supports cell survival and maintenance in the hypoxic environment of tumor cells when oxygen is not a readily available electron acceptor for NADH. PYCR1 generates NAD + for the TCA cycle in the absence of the electron transport chain, generating proline as a byproduct .…”
Section: Introductionmentioning
confidence: 99%